2017
DOI: 10.3389/fncel.2017.00054
|View full text |Cite
|
Sign up to set email alerts
|

The GABAergic Hypothesis for Cognitive Disabilities in Down Syndrome

Abstract: Down syndrome (DS) is a genetic disorder caused by the presence of a third copy of chromosome 21. DS affects multiple organs, but it invariably results in altered brain development and diverse degrees of intellectual disability. A large body of evidence has shown that synaptic deficits and memory impairment are largely determined by altered GABAergic signaling in trisomic mouse models of DS. These alterations arise during brain development while extending into adulthood, and include genesis of GABAergic neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 287 publications
(478 reference statements)
5
106
0
1
Order By: Relevance
“…S2). within the hippocampus of Ts65Dn mice (81). However, we saw increases in both these subunit mRNAs by MCS, regardless of genotype or age.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…S2). within the hippocampus of Ts65Dn mice (81). However, we saw increases in both these subunit mRNAs by MCS, regardless of genotype or age.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with DS have documented GABAergic dysfunction, which results in impairments of synaptic plasticity and an imbalance of excitation and inhibition (80,81). Trisomic mice mimic GABAergic dysfunction seen in human DS, including changes in subcellular localization of GABA A receptors away from the dendritic shaft to the spine neck and increases of GABA-evoked firing (81,82).…”
Section: Discussionmentioning
confidence: 99%
“…). Importantly, as in human postmortem studies, an imbalance of excitatory and inhibitory neurons, impaired neurogenesis, synaptogenesis, and altered dendritic development are also observed in mouse models of Down syndrome (detailed reviews are available elsewhere) …”
Section: Mouse Models Of Down Syndromementioning
confidence: 99%
“…Importantly, as in human postmortem studies, an imbalance of excitatory and inhibitory neurons, impaired neurogenesis, synaptogenesis, and altered dendritic development are also observed in mouse models of Down syndrome (detailed reviews are available elsewhere). 9,[17][18][19]41,56,58,59 The Ts65Dn mouse (B6EiC3Sn a/A-Ts [17 16 ]65Dn/J) has historically been very important in the study of Down syndrome as it is trisomic for 90 protein coding genes on Mmu16 (approximately 55% of orthologous genes to Hsa21). However, Ts65Dn mice contain an extra copy of 60 genes (35 protein coding) located on Mmu17 (orthologous to Hsa6) that are not triplicated in people with Down syndrome and the resultant Ts65Dn phenotypes may be more severe than those seen in the human condition or possess spurious phenotypes not relevant to Down syndrome.…”
Section: Mouse Models Of Down Syndromementioning
confidence: 99%
“…Strikingly, PTZ treatment normalized the lifespan of Bmal1cKO animals (average lifespan 22 vs. 25 months after TM treatment, respectively, Log‐rank test, p = .049) while no differences were found in controls (Figure b). The long‐term effect of this protocol of PTZ treatment, at nonepileptic doses, is not surprising at it was previously shown to produce long‐lasting cognitive improvements after drug withdrawal in rodents (Colas et al, ; Contestabile, Magara, & Cancedda, ; Fernandez et al, ; Ruby et al, ). Interestingly, we also found that PTZ‐treated Bmal1cKO mice displayed significantly reduced levels of reactive gliosis in different areas of the cortex as well as in the hypothalamus in comparison to untreated animals at 4 months after TM treatment (i.e., 2 months after the PTZ administration; Figure c).…”
Section: Resultsmentioning
confidence: 69%